Characteristics and pre-travel preparation of travelers at a Canadian pediatric tertiary care travel clinic: A retrospective analysis. Issue 2 (March 2016) - Ma, Xiao Wei; Pell, Lisa G.; Akseer, Nadia; Khan, Sarah; Lam, Ray E.; Louch, Debra; Science, Michelle; Morris, Shaun K.
Summary: Background: International travelers are susceptible to a wide spectrum of travel related morbidities. Despite rising number of international travelers in Canada, the demographics, risk profiles, and preventative strategies of high-risk traveler groups, including pediatric travelers visiting friends and relatives (VFRs) are not well described. Methods: A descriptive analysis was conducted on pre-travel consultations completed between January 2013 and August 2014 at a large pediatric tertiary care center in Toronto, Canada. Data on demographics, travel characteristics, and pre-travel interventions were extracted from 370 pre-travel consultations. Results were compared between all VFR and non-VFR travelers, as well as between children traveling to visit friends and relatives, for vacation, and for education and/or volunteer purposes. Results: Forty-eight percent of consultations were for children <18 years of age ( n = 177), of which 31% were for young children (<5 years of age). Young children were more likely to travel to visit friends and/or relatives than for other purposes (29% vs 9%, p < 0.0001). Children VFRs (cVFRs) were more likely to travel for >28 days than children traveling for vacation (43% vs 1%, p < 0.0001), and children traveling for education/volunteer purposes (43% vs 21%, p = 0.03). Around half of cVFRs traveled to destinations in Asia (51%). The majority stayed with locals, friends and/or relatives (85%), and nearly all traveled to urban destinations (98%). The most prescribed interventions for children were azithromycin (84%), Dukoral (66%), and the hepatitis A vaccine (60%). Atovaquone/proguanil was the most commonly prescribed antimalarial for children. Conclusion: Children that travel to visit friends and relatives represent a unique travel group and may require specific considerations during pre-travel preparations. Our findings can help develop targeted pre-travel strategies for children VFRs.